THE ROLE OF TAX DEDUCTIONS IN SHAPING INDIVIDUAL FINANCIAL BEHAVIOR IN INDIA - Madiwalar, Meenaxi Shivappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tax deductions are a key fiscal tool that influences how individuals in India manage their finances, save, and invest. By allowing taxpayers to reduce their taxable income through specific expenditures and investments, deductions encourage financial behavior aligned with both personal goals and national economic objectives. Under the Income Tax Act, 1961, various sections—such as 80C for investments in provident funds and life insurance, 80D for health insurance premiums, and 80E for education loans—provide structured incentives that shape financial decisions. These provisions not only offer immediate tax relief but also motivate long-term financial planning, contributing to capital formation, social welfare, and economic stability. The impact of tax deductions is particularly significant in guiding savings behavior. Many individuals start investing primarily to avail tax benefits, gradually building habits of disciplined saving. Instruments like the Public Provident Fund (PPF) and Equity Linked Savings Schemes (ELSS) gain popularity because of the dual advantage of returns and deductions. Similarly, deductions on home loan interest and principal repayment encourage home ownership, while those on health insurance premiums promote better risk management. Furthermore, deductions under 80G stimulate charitable donations, reflecting how fiscal policies can promote social responsibility. However, the benefits of tax deductions are unevenly distributed, favoring individuals in formal employment with higher taxable incomes, while informal workers and low-income households often fail to utilize these provisions fully. The recent introduction of the new tax regime without deductions has also altered financial behavior, as taxpayers now weigh simplicity against the benefits of deductions. The Study concludes that tax deductions serve as more than just a means of reducing taxes; they actively influence individual choices related to savings, investments, and consumption. This interplay highlights the power of tax policy as a driver of financial behavior in India.